The usefulness of leptin measurements and ultrasound fat thickness for assessment of body fat reserves of Awassi lambs - Kara, Çağdaş; Gençoğlu, Hidir; Orman, Abdülkadi̇r; Temi̇zel, Ethem Mutlu; Ünal, Ci̇han; Çalişkan, Gülsüm Ülke (Informa UK Limited, 2018)
The objective of this study was to investigate the usefulness of leptin measurements for predicting back fat thickness and the amount of carcase fat in lambs with varying body weights (BWs). Blood samples were taken from 20 male Awassi lambs at 20, 25, 30, 35, and 40 kg BW. Tail, omental, dissected, and total fat were measured at slaughter (40 kg BW). Ultrasound fat thickness (UFT) increased with BW (p < .05) whereas leptin concentration tended to increase (p = .09). Serum leptin concentration was correlated with BW for 25, 30, 35, and 40 kg BW (r = 0.53, 0.52, 0.51 and 0.61, respectively; p < .05) and with UFT for 30, 35, and 40 kg BW (r = 0.50, 0.51 and 0.59, respectively; p < .05); therefore it appears that leptin concentration is not a suitable predictor for BW and UFT in low BW lambs. In addition, similar correlations were found for leptin concentration and hot carcase, omental, dissected, and total fat weights (r = 0.62, 0.64, 0.66 and 0.76, respectively; p < .05) but not for tail fat (p >.05 for 40 kg BW). The introduction of UFT and BW as independent variables in addition to leptin in the multiple regression equations improved the predictions for carcase fat only (57.6%, p < .05; 57.8%, p < .05 and 60.7%, p > .05 for leptin, leptin + UFT and leptin + BW, respectively). Leptin was a single predictor for omentum and dissected fat (41.4%, p < .05 and 43.5%, p < .05 respectively) whereas no improvement was observed for tail fat (p > .05). The other variables (UFT and BW) were not a predictor (p > .05) except for total fat (p > .05). These results indicate that serum leptin concentration in association with BW and UFT could be used to estimate total fat (tail, omental and dissectible carcase fat) in male Awassi lambs.
Keywords: fat tissues; Awassi; carcase fat amount; leptin; SF1-1100; Animal culture; 2. Zero hunger